Triune eternality : God's relationship to time in the theology of Karl Barth - Griswold, Daniel M. (Minneapolis Fortress Press, 2015)
The theology of Karl Barth is an important resource for theological reflection on the complicated problem of God's relationship to time; yet much of what Barth says is difficult to unravel. His statements on God and time, and on God and eternity, are spread throughout his writings, finding their place in theological discussions of a variety of doctrinal topics. These difficulties have led some to despair of adequately articulating Barth's position, while leading others to propose overly broad or simplistic renderings. Triune Eternality argues that a proper comprehension of Barth's theological conception of time and eternity is best achieved by understanding three important contexts: the doctrinal, the conceptual, and the developmental. By understanding those contexts, it may be seen that Barth's understanding of time and eternity is how he expresses theological convictions that are more basic to Christian theology. In short, for Barth "time and eternity" are not so much philosophical or scientific concepts but theological terms that point to fundamental realities. This work proceeds from the conviction that in Barth we have a twofold opportunity: to allow earlier answers to speak to our own recent questions and to use our contemporary perspective to gain insight on historic contributions.
Revision of the author's thesis (doctoral)--Southern Methodist University, 2010 under title: Perichoretic eternality : God's relationship to time in Karl Barth's Church dogmatics.
Includes bibliographical references (pages 251-260) and index.
Keywords: Barth, Karl, -- 1886-1968 -- Criticism and interpretation; God (Christianity) -- Eternity; Time -- Religious aspects -- Christianity; Eternity